A New Model to Calibrate a Reference Standard for Bovine Tuberculin Purified Protein Derivative in the Target Species - Frankena, Klaas; Jacobs, Liesbeth; van Dijk, Tonny; Good, Margaret; Duignan, Anthony; de Jong, Mart C. M. (Frontiers in Veterinary Science, 2018)
Since 1986, use of a Bovine International Standard (BIS) for bovine tuberculin has been required to ensure national and international uniformity regarding the potency designation of bovine tuberculin Purified Protein Derivate (PPDb) preparations produced by multiple manufacturers. The BIS is the unique golden standard in the guinea pig potency assay, representing 100% potency, where potencies of production batches are calculated as relative potencies in comparison with the potency of the BIS which was set at 32,500 international Unit (IU) per mg. The stock supply and lifetime of the BIS is limited. The aim of this study was to develop a model to determine the potency of a newly produced in-house Reference Standard (RS) for PPDb with great accuracy in the target species (cattle) and to proof its precision and accuracy in the guinea pig potency test. First simulations were done to estimate the required number of cattle needed. Then, 30 naturally bTB infected cattle were subjected to a tuberculin skin test using multiple injections of both the RS and the BIS. Both were applied randomly in the same volume and concentration (1 dose). The potency of the RS against the BIS was directly derived from the LSMEANS and was estimated as 1.067 (95% CI: 1.025-1.109), equal to a potency of 34,700 ± 1,400 IU/mg. In six guinea pig potency assays the RS was used to assign potencies to production batches of PPDb. Here, precision and accuracy of the RS was determined according to the parallel-line assay. Relative potencies were estimated by taking the antilog of the common slope. The corresponding 95% confidence intervals were obtained according to Fieller’s theorem. In sensitized guinea pigs, the relative potency of the RS against the BIS was 1.115 (95% CI: 0.871-1.432), corresponding to an absolute potency of 36,238 IU/mg (95% CI: 28,308-46,540). In conclusion: the method used to determine the potency of the RS against the BIS in naturally bTB infected cattle, resulted in a highly accurate potency estimate of the RS. The RS can be used in the guinea pig test to assign potencies to PPDb production batches with high precision and accuracy.